A clinical and histological evaluation of platelet-rich fibrin and CGF for root coverage procedure using coronally advanced flap: A split-mouth design - Dhanadivya Krishnakumar; Jaideep Mahendra; Geetha Ari; Rajapriya Perumalsamy (Wolters Kluwer Medknow Publications, 2019)
The management of gingival recession associated with esthetic concerns and root hypersensitivity is challenging and its sequelae are based on the assessment of etiological factors and the degree of tissue involvement. Procedures using pedicle flaps, free soft-tissue grafts, combination of pedicle flaps with grafts, barrier membranes, and the use of platelet concentrates are all effective for this purpose. The use of the second-generation platelet concentrate, platelet rich fibrin (PRF) has been widely used. Lately, concentrated growth factor (CGF) has evolved as a promising regenerative material, wherein it also acts as a scaffold and accelerates wound healing due to its dense fibrin meshwork. A 21-year-old male patient presented with bilateral multiple gingival recessions due to faulty tooth brushing. Coronally advanced flap with Zuchelli's technique was planned as a treatment modality. Platelet concentrates PRF and CGF were placed bilaterally during the procedure, and the outcome of the treatment was compared. The percentage of root coverage was clinically evaluated, and histological evaluation was also done to assess the density of fibrin meshwork in the platelet concentrates. Nearly 100% of root coverage was achieved with both PRF and CGF membrane 3 months postoperatively. However, CGF showed satisfactory wound healing by the 10th-day postoperatively compared to PRF. As CGF operates on varying centrifugation to separate cells in the venous blood, thereby resulting in fibrin-rich blocks that are much larger, denser, and richer in growth factors as also shown histologically.